INDEPENDENCE OF BUDGET MANAGEMENT TO REALIZE THE INDEPENDENCE OF JUDICIAL INSTITUTIONS - Rumadhan, Ismail (Jurnal Hukum dan Peradilan, 2021)
The Supreme Court in carrying out the function of judicial power is carried out independently so that it is not possible for intervention from other parties that can affect its function. However, the independence of the Supreme Court has not been fully strung together in accordance with the concept of independence in the exercise of judicial power. This can be seen in the Supreme Court's budget, the amount of which is still determined by the government. This condition will certainly affect its independence, because the budget is a support for the Supreme Court in carrying out the functions of judicial power. In this discussion, the method used is normative juridical. The benefit of this research is that it can become a reference for the Supreme Court to form an independent budget pattern so that it can carry out its functions independently. The conclusion of this study is that the Supreme Court has not been able to carry out its functions independently as outlined in Article 24 paragraph (1) of the 1945 Constitution, so it is necessary to change regulations by aligning the rules so that the Supreme Court can prepare its budget independently.